The Baltic states : Estonia, Latvia and Lithuania - Smith, David J. (David James), 1968-; Pabriks, Artis; Purs, Aldis; Lane, A. T. (London : Routledge, Taylor & Francis Group, 2002)
Annotation Since the end of the Cold War there has been an increased interest in the Baltics. The Baltic Statesbrings together three titles, Estonia, Latvia and Lithuania, to provide a comprehensive and analytical guide integrating history, political science, economic development and contemporary events into one account. Since gaining their independence, each country has developed at its own pace with its own agenda and facing its own obstacles. The authors examine the tensions accompanying a post-communist return to Europe after the long years of separation and how each country has responded to the demands of becoming a modern European state. Estonia was the first of the former Soviet republics to enter membership negotiations with the European Union in 1988 and is a potential candidate for the next round of EU expansion in 2004. Lithuania and Latvia have also expressed their desire for future membership of NATO and the EU.
Estonia : independence and European integration / David J. Smith (xxxii, 198 pages) -- Latvia : the challenges of change / Artis Pabriks and Aldis Purs (xiv, 170 pages) -- Lithuania : stepping westward / Thomas Lane (xl, 246 pages).
Includes bibliographical references and index.
Online resource; title from PDF title page (ebrary, viewed November 26, 2013).
Print version record.
English.
eBooks on EBSCOhost
Keywords: Baltic States; Estonia -- History -- 1991-; Latvia -- History -- 1991-; Lithuania -- History -- 1991-; Estonie -- Histoire -- 1991-; Lettonie -- Histoire -- 1991-; Lituanie -- Histoire -- 1991-; HISTORY -- Europe -- Eastern; HISTORY -- Europe -- Former Soviet Republics; HISTORY -- Europe -- Russia & the Former Soviet Union; Baltic States; Estonia; Latvia; Lithuania; Since 1991; Electronic books; History